2013
DOI: 10.4314/ahs.v13i2.43
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene practices among community Health Officers in Rivers State, Nigeria

Abstract: Background: Health care associated infections are most commonly transmitted by the hands of Health care workers and other hospital personnel. Objective: To investigate compliance with hand hygiene guidelines and methods of hand hygiene practice among community health officers in Rivers State Nigeria. Methods: Self administered questionnaires were distributed to 68 community health officers. The questionnaires consisted of 19 items which contained information on bio-demographic characteristics and hand hygiene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…A qualitative study in India identified interrupted supply of water, inadequate number of washbasins and the distance between patients and wash hand basins as barriers to HH practices [ 5 ]. Similar barriers as well as inadequate supply of alcohol-based hand rubs (ABHR) were even reported in a high resource setting [ 6 ]. In addition to the structural barriers, inadequate time [ 2 ], staff attitude, knowledge, education of HCW and workload issues [ 1 ] are functional impediments to effective HH practices.…”
Section: Introductionmentioning
confidence: 65%
“…A qualitative study in India identified interrupted supply of water, inadequate number of washbasins and the distance between patients and wash hand basins as barriers to HH practices [ 5 ]. Similar barriers as well as inadequate supply of alcohol-based hand rubs (ABHR) were even reported in a high resource setting [ 6 ]. In addition to the structural barriers, inadequate time [ 2 ], staff attitude, knowledge, education of HCW and workload issues [ 1 ] are functional impediments to effective HH practices.…”
Section: Introductionmentioning
confidence: 65%
“…None of the work elements in the current study were performed in complete compliance to WHO's guidelines at all times, proving that compliance to basic hygiene often falls short of acceptable standards [15].The theatre staffs views on Patient safety culture…”
Section: Discussionmentioning
confidence: 80%
“…Surgical site infections can be prevented however, studies show that hand hygiene is not followed optimally in developing countries [15]. Compliance to basic hand hygiene should therefore be prioritised in order to optimize patient safety.…”
Section: Hygiene Routines Specific For Intraoperative Care According mentioning
confidence: 99%
“…DOI: https://dx.doi.org/10.17352/2455-5479.000095 considered to reduce infection transmissibility in the hospital setting [5,6]. Although hand hygiene can be described as an effective, simple, cheap and not time consuming HAI control strategy most studies show low compliance rate of between 40% and 70% [7,8]. HCW have reported several factors that negatively impact their adherence with recommended practices including but not limited to; inadequate knowledge and lack of awareness, hand washing agents cause irritation and dryness, sinks are inconveniently located, lack of soap and paper towels, not enough time, over workload with understaffi ng, lack of knowledge of guidelines/protocols, and forgetfulness [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It affects 5-15% of hospitalized patients in developed country with higher fi gures quoted for developing countries [14,15]. Diarrhoea diseases and respiratory tract infections are among the leading contributors to the global burden of disease and poor water supply related to hand hygiene represents 7% of the risk factors [7].…”
Section: Introductionmentioning
confidence: 99%